Sharpening Tools for Landscaping and Gardening - Geoffrey C. Denny (EDIS)
ENH-1120, a 5-page illustrated fact sheet by Geoffrey C. Denny, discusses the required equipment and supplies to sharpen common landscape and garden tools, as well as the proper sharpening techniques. Published by the UF Department of Environmental Horticulture, May 2009.